INTERCONNECTION SCIENCE AND ISLAM: RELIGIUSITY AND MASTER CONTROL CHEMICAL CONTENT - Aswirna, Prima (Proceedings of the International Conference on Green Technology, 2017)
This research departs from the search for empirical evidence of the interconnection between science and general science (particularly Chemistry). The facts show that until now the achievement of student learning in Basic Chemistry course is still relatively low. Later this research using model trait treatment interaction to improve learning outcomes. This research is run at State Islamic University Imam Bonjol Padang. The population of this study as many as 97 people although only complains 66 students included in this study. Where the research this involves only students who are following the teaching of Basic Chemical. Sampling technique is done by using random side simple. Then the data collection through questionnaires and interviews. Data analysis techniques using Pearson correlation. Results of the study found that: (1) Distribution of mean religiosity of students is high. (2) Chemical scholarly content Mastery of students increased if the teaching methods are adapted to the prior knowledge possessed. (3) control of the content I LMU Chemistry students increased after getting learning model self-learning (self-learning) for students with high starting capabilities. (4) the capability of Chemistry student content increased when they learned with regular methods of teaching plus tutorials for students with lower initial ability. (3) There is a relationship between religiosity and mastery of scientific content Chemistry. Where the higher the student religiosity, the higher the learning (*)